The Correlation Between Knowledge, Attitudes, and Behaviors Regarding Added Sugar and The Risk of Diabetes Mellitus in Adolescents - Ernanda, Elsalma; Muzaenah, Tina (Proceedings Series on Health & Medical Sciences, 2026)
Background: Diabetes mellitus is a growing health concern among adolescents, with excessive added sugar consumption being a major contributing factor. Knowledge, attitudes, and behaviors related to added sugar intake play an important role in reducing the risk of diabetes. Method: This study used a quantitative correlational design with a cross-sectional approach. A total of 159 adolescents from SMP Negeri 1 Cilongok were selected using proportional random sampling. Data were collected using questionnaires measuring knowledge, attitudes, behaviors, and diabetes risk using the PRESTARt instrument. Data were analyzed using the chi-square test. Results: The results showed a significant relationship between knowledge and behavior with the risk of diabetes mellitus (p = 0.032 and p = 0.002). However, no significant relationship was found between attitudes and diabetes risk (p = 0.203). Conclusion: Knowledge and behavior regarding added sugar consumption are significantly associated with the risk of diabetes mellitus in adolescents, while attitudes do not show a significant relationship.